Enhancing elementary students’ reading interest through the spin the wheel digital game - Juniman; Dewi Silvi Listia; Alfi Syahrin (Graduate School, Universitas Negeri Yogyakarta, 2025)
This study aims to examine the planning, implementation, and challenges of using the Spin the Wheel digital game to enhance elementary school students’ interest in reading Indonesian language textbooks. A descriptive qualitative approach was employed involving fourth-grade students, a classroom teacher, and a school principal at an elementary school in Bireuen Regency, Indonesia. Data were collected through observations, in-depth interviews, and documentation, and were analyzed using qualitative descriptive techniques with source and method triangulation to ensure trustworthiness. The findings reveal that the Spin the Wheel digital game was systematically integrated into Indonesian language instruction and supported created an interactive, enjoyable, and participatory learning environment. The implementation of the game increased students’ reading interest, concentration, reading comprehension, and self-confidence while fostering positive attitudes toward reading activities. Several challenges were identified, including limited instructional time, inadequate supporting facilities, and differences in students’ reading abilities. However, these challenges were effectively addressed through adaptive teaching strategies and institutional support. The study concludes that the Spin the Wheel digital game is an effective gamification-based learning medium for promoting reading interest among elementary school students. This study contributes to the growing literature on gamification in elementary education by providing empirical evidence of how digital game-based learning can support literacy development and create more engaging reading experiences in primary school classrooms.